Ultrasound Imaging of Quadriceps Tendon in a Recreational Golfer - Shawn Felton; Arie van Duijn (CINQUILL Medical Publishers Inc., 2021)
The patient was a 69-year-old recreational golfer who injured his right . While walking between the 9th and 18th holes, he slipped on pine straw. Ultrasound images of the quadriceps tendon post-injury revealed a full-thickness tear of the Quadriceps tendon, Rectus Femoris and Vastus intermedius. The diagnosis was confirmed through MRI arthrogram imaging. The hypoechoic finding in the ultrasound exam demonstrated the imaging to be as precise in diagnosing a full thickness tear as the MRI. The patient underwent surgical repair of the Quadriceps Tendon and is currently progressing in rehabilitation.